Implementation of Writing Learning in Class V Imaginative Learning Models at MI/SD - Muhd. Hayyanul Damanik; Nur Annisa Ibsan; Anggi Anisa; Nur Pusfita Sari (Universitas Muhammadiyah Enrekang, 2023)
This research aims to investigate the level of success of students in writing learning through the implementation of an imaginative writing learning model. This topic was chosen due to the difficulties in developing writing skills among elementary school children and the prevalence of teachers relying on less innovative lecture-based teaching methods. The study focuses on the application and implementation of the imaginative writing learning model in the fifth grade class of Usman bin Affan at SD IT Islamic Center, located on Jl. Selamat Ketaren, Kec. Percut Sei Tuan, Kabupaten Deli Serdang, North Sumatra. The research adopts a qualitative approach with a descriptive method, which means that the obtained data will be reported objectively and analyzed descriptively to obtain a comprehensive understanding of the existing facts. The sources of data for this study are teachers and students. The data collection techniques include interviews, observations, and documentation. As for data analysis, the research utilizes non-statistical methods, specifically descriptive data analysis. The results of this study indicate that the implementation of the imaginative writing learning model in the fifth grade class of Usman bin Affan at SD IT Islamic Center, led by Ustadz Muhammad Khaidir, has been successful. The students have demonstrated improvement in their writing skills through the utilization of imaginative techniques employed in the learning process. The students have shown high interest, active engagement, and the ability to produce creative and imaginative writings. This research is expected to contribute to the development of innovative and relevant teaching methods, particularly in the context of writing learning at the elementary school level. The findings of this study can serve as a reference for teachers in designing engaging, creative, and motivating writing lessons, enabling students to enhance their writing skills effectively.